At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Simplify 2x-- yfor x = 3 and y=-2.
•20
•14
•16
•10


Sagot :

Jr344
2(3) - (-2) = 8 … r u missing part of the question?
ItzTds

Answer:

8 (none of the above)

Step-by-step explanation:

Given that,

→ x = 3

→ y = -2

Let's solve the equation,

→ 2x - y

→ 2(3) -(-2)

→ 6 + 2

→ 8 is the answer.